2000
DOI: 10.1074/jbc.m909882199
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 2 Interacts with Sorcin, a Modulator of the Ryanodine Receptor

Abstract: Perturbed Ca2؉ homeostasis is a common molecular consequence of familial Alzheimer's disease-linked presenilin mutations. We report here the molecular interaction of the large hydrophilic loop region of presenilin 2 (PS2) with sorcin, a penta-EF-hand Ca 2؉ -binding protein that serves as a modulator of the ryanodine receptor intracellular Ca 2؉ channel. The association of endogenous sorcin and PS2 was demonstrated in cultured cells and human brain tissues. Membrane-associated sorcin and a subset of the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 59 publications
(39 reference statements)
2
65
1
Order By: Relevance
“…Some studies have demonstrated that FAD-related mutant PS may sensitize neurons to apoptosis by perturbing intracellular calcium homeostasis (13,(31)(32)(33). We found that dantrolene treatment suppressed sel-12(ar131)-induced apoptosis, which means that by abnormal regulation of calcium release from the ER, sel-12(ar131) predisposes embryo cells to apoptosis.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies have demonstrated that FAD-related mutant PS may sensitize neurons to apoptosis by perturbing intracellular calcium homeostasis (13,(31)(32)(33). We found that dantrolene treatment suppressed sel-12(ar131)-induced apoptosis, which means that by abnormal regulation of calcium release from the ER, sel-12(ar131) predisposes embryo cells to apoptosis.…”
Section: Discussionmentioning
confidence: 59%
“…Instead, the abnormalities in hippocampal synaptic plasticity are likely the result of the perturbed endoplasmic reticulum Ca 2+ regulation previously documented in studies of cultured neurons expressing FAD PS1 mutations. Those studies showed that PS1 mutations cause Ca 2+ to accumulate at higher levels in the endoplasmic reticulum resulting in an enhanced release of Ca 2+ in response to muscarinic agonists (Guo et al, 1997;Begley et al, 1999;Leissring et al, 2001), as well as enhanced Ca 2+ -induced Ca 2+ release through ryanodine receptors (Chan et al, 2000;Pack-Chung et al, 2000). Apparently, wild-type PS1 functions as a Ca 2+ leak channel in the endoplasmic reticulum membrane, and FAD-linked PS1 mutations impair this Ca 2+ leak function (Tu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some PS-associated proteins (e.g. calpain, calmyrin, and sorcin) also bind calcium, and PS has been implicated in intracellular calcium homeostasis (27,(47)(48)(49)(50)(51). In this regard, CALP might have a function in PS-mediated calcium modulation.…”
Section: Effect Of the Overexpression Of Calp On Metabolism Of Ps Polmentioning
confidence: 99%